2002
DOI: 10.1124/mol.61.6.1423
|View full text |Cite
|
Sign up to set email alerts
|

The Muscarinic Acetylcholine Receptor-Stimulated Increase in Aquaporin-5 Levels in the Apical Plasma Membrane in Rat Parotid Acinar Cells Is Coupled with Activation of Nitric Oxide/cGMP Signal Transduction

Abstract: The present study investigated the role of nitric oxide (NO)/cGMP signal transduction in the M 3 muscarinic acetylcholine receptor (mAChR)-stimulated increase in aquaporin-5 (AQP5) levels in the apical plasma membrane (APM) of rat parotid glands. Pretreatment of rat parotid tissue with the NO scavenger 2-(4carboxyphe-nyl)-4,4,5,5-tetramethyl-imidazoline-1-oxyl-3-oxide potassium inhibited both acetylcholine (ACh)-and pilocarpine-induced increases in AQP5 in the APM. NO donors [3-morpholinosydnonimine (SIN-1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 36 publications
6
50
0
Order By: Relevance
“…Conversely, A23187, a calcium ionophore (44), alone increases the amount of AQP5 in the APM and decreases the amount of AQP5 in the Triton X-100-insoluble fraction (21). These findings indicate that an increase in the intracellular calcium concentration ([Ca (45,47). This increase coincides with the increased AQP5 levels in the APM in rat parotid gland cells.…”
Section: Intracellular Signals For the Translocation Of Aqp5 Towards supporting
confidence: 51%
“…Conversely, A23187, a calcium ionophore (44), alone increases the amount of AQP5 in the APM and decreases the amount of AQP5 in the Triton X-100-insoluble fraction (21). These findings indicate that an increase in the intracellular calcium concentration ([Ca (45,47). This increase coincides with the increased AQP5 levels in the APM in rat parotid gland cells.…”
Section: Intracellular Signals For the Translocation Of Aqp5 Towards supporting
confidence: 51%
“…The transmembrane water flux via the regulation of aquaporin quantity and activity endows plants with a remarkable capacity to modulate water absorption, transport and compartmentation within tissues. In animal studies, the role of NO/cGMP signal transduction in the M3 muscarinic acetylcholine receptor-stimulated increase in AQP5 levels in the apical plasma membrane of rat parotid glands was reported [34]. Pretreatment of rat parotid tissue with the NO scavenger inhibited acetylcholine-induced increases in AQP5 in the apical plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…NO/cGMP signal transduction has a crucial role in Ca 2+ homeostasis in the M3 muscarinic acetylcholine-stimulated increase in AQP5 levels in the apical plasma membrane of rat parotid glands [34]. NO plays a role in seed germination, yet little is understood about how it functions.…”
Section: Effects Of No On Pip Transcript Levels In Germinating Seedmentioning
confidence: 99%
“…Finally, AQP5, which has a major role in the generation of saliva, tears and pulmonary secretions, has been shown to translocate to the plasma membrane of rat parotid cells upon stimulation with the M3 muscarinic GPCR agonist, acetylcholine, or the adrenergic receptor agonist, adrenaline (Ishikawa et al, 1999). Internalisation of AQP5 was observed following prolonged exposure to acetylcholine (Ishikawa et al, 1998a, Ishikawa et al, 2002.…”
Section: What Triggers Aqp Translocation?mentioning
confidence: 99%
“…The use of specific inhibitors has revealed that the mechanism of acetylcholine-induced AQP5 translocation is mediated by cGMP, calmodulin and protein kinase G (Ishikawa et al, 2002).…”
Section: Protein Kinase Gmentioning
confidence: 99%